A model to analyze foodsheds and self-sufficiency (case study: Tehran province) - Maryam Akbarpoor; Hadi Veisi; Abdolmajid Mahdavi Damghani; Mohammadreza Nazari (علوم محیطی)
Introduction: Localization of the food system has become in line with sustainable agriculture for many reasons including ecological advantages, economic benefits, and social considerations. Yet the question is that to what extent food can be locally produced. To answer this question, the concept of foodshed can be considered. The concept provides a framework for analyzing local food production at any scale. The foodshed is a land that can supply all or parts of a given population's nutritional needs within a given geographical area. So far, no foodshed study has been conducted in Iran, so this study proposed a model to study foodsheds. By taking a sustainable food system into account, the current research examined the concept of foodshed, the status of food production and consumption in Tehran Province, and the capacity of this province to meet its nutritional needs. Material and methods: The model was used in Tehran Province using a unit named "plant equivalent" to calculate and compare the amount of food produced in the study area and the nutritional requirement of the province’s population. Production of each crop (based on the plant equivalent unit) in each region was calculated by multiplying the crop cultivation land area in the crop yield. The amount of need for each plant equivalent unit in each region was calculated by multiplying the population of that area in the weight of food that is needed of a person in a year. Then, using self-sufficiency formulas, we estimated how much of the population's needs are being supported by the existing production. To calculate self-sufficiency, a concept known as threshold production was used. Calculation of threshold production was done with Matlab using conditional programming and coding. Excel, Matlab, and GIS were used in this research. Results and discussion: One of the most important achievements of the present study was the foodshed assessment of Tehran Province considering its increasing population and providing food security in this province. In the present study, which was carried out on a provincial scale, self-sufficiency in providing the desired food basket for the population of Tehran Province was 22% and the highest and lowest self-sufficiency was estimated in Pishva and Tehran counties, respectively. Self-sufficiency percent in producing crops to provide the desired food basket in Tehran Province was higher in fodder corn (100%) (self-sufficient), vegetables (79%), fruits (56%), barley straw (53%), wheat straw (45%), barley grain (16%), wheat bran (8%), wheat grain (5%), forage crops except corn (4%), rapeseed meal (0/1%), rapeseed (0/06%), respectively. However, in legumes, rice hull, root, pulp, and molasses of sugar beet, corn, and soybean meal self-sufficiency percent was estimated zero percent, meaning non-self-sufficient or total dependence. Conclusion: The results of this study indicated that the percentage of foodshed self-sufficiency in providing the desired food basket for the population of Tehran Province was 22%. Although localization has benefits, it seems that considering the small area and the overcapacity population of Tehran Province and the environmental issues (water scarcity and soil erosion), the boundaries of Tehran Province foodshed should be broadened and the foodshed radius must be increased.